Analisis Sistem Pelaporan Keuangan Zakat Fitrah dan Kesesuaiannya dengan PSAK 109 (Studi pada Masjid Nurul Faridah Talinro Kecamatan Ulaweng Kabupaten Bone) - Irawan, Adhe; Ananda, Dhea Tri; Hasbi, Hartas (Universitas Serambi Mekkah, 2024)
The aim of this research is to assess the Nurul Faridah Mosque's zakat fitrah financial reporting system and its compliance with PSAK 109. Aspects of recognition, measurement, presentation and disclosure of zakat transactions in financial reports are the focus of the evaluation. This research uses case study methodology and qualitative descriptive techniques. Direct observation of financial recording procedures, in-depth interviews with mosque imams, treasurers and mosque administrators, as well as examination of financial report documents for 2021–2023 were used to collect data. Research findings indicate that the Nurul Faridah Mosque's zakat financial reporting system is not fully compliant with PSAK 109. The following are the main areas of inconsistency: (1) zakat assets that have not been assessed at fair value are recognized; (2) measurements of zakat distribution are not recorded systematically; (3) financial reports are presented without distinguishing zakat funds from other funds; and (4) incomplete information disclosed in the notes to the financial statements. The lack of codified accounting regulations, manual recording methods, and the lack of human resources who have knowledge of sharia accounting principles are the main challenges in implementing PSAK 109. A number of system improvements suggested in this research include: (1) PSAK 109 HR training; (2) codified accounting rules and procedures; (3) creation of a digital zakat accounting information system; and (4) strengthening the internal control system. The implementation of these suggestions is expected to improve the quality of zakat financial reporting in accordance with relevant requirements.